Subspecies and Distribution. M.l.longicaudusMerriam,1888—widelydistributedfromCAlaskaStoCNewMexico,USA. M.l.abditusA.B.Howell,1923—N&CcoastalOregon,USA. M.l.alticolaMerriam,1890—SEUtahandNArizona,USA. M.l.angusticepsBailey,1898—ScoastalOregonandNcoastalCalifornia,USA. M.l.bailey:Goldman,1938—NCArizona,USA. M.l.bernardinusMerriam,1908—SCCalifornia,USA. M.l.coronariusSwarth,1911—Coronation,Warren,andForresterIsinSEAlaska,USA. M.l.halliHayman&Holt,1941—SEWashingtonandNEOregon,USA. M.l.incanusLee&Durrant,1960—HenryMtsofSCUtah,USA.M.latusHall,1931—CNevadaandWUtah,USA. M.l.leucophaeusJ.A.Allen,1894—knownonlyfromGrahamMts,SEArizona,USA. M.l.littoralisSwarth,1933—coastalSEAlaska,USA. M.l.macrurusMerriam,1898—fromCBritishColumbiaStoEWashington,USA. M.l.sierraeKellogg,1922—fromtheOregonborderStoECCalifornia,USA. M. l. vellerosus J. A. Allen, 1899 — widely distributed from EC Alaska SE to SE British Columbia and SW Alberta, Canada. in Cricetidae - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
Subspecies and Distribution. M.l.longicaudusMerriam,1888—widelydistributedfromCAlaskaStoCNewMexico,USA. M.l.abditusA.B.Howell,1923—N&CcoastalOregon,USA. M.l.alticolaMerriam,1890—SEUtahandNArizona,USA. M.l.angusticepsBailey,1898—ScoastalOregonandNcoastalCalifornia,USA. M.l.bailey:Goldman,1938—NCArizona,USA. M.l.bernardinusMerriam,1908—SCCalifornia,USA. M.l.coronariusSwarth,1911—Coronation,Warren,andForresterIsinSEAlaska,USA. M.l.halliHayman&Holt,1941—SEWashingtonandNEOregon,USA. M.l.incanusLee&Durrant,1960—HenryMtsofSCUtah,USA.M.latusHall,1931—CNevadaandWUtah,USA. M.l.leucophaeusJ.A.Allen,1894—knownonlyfromGrahamMts,SEArizona,USA. M.l.littoralisSwarth,1933—coastalSEAlaska,USA. M.l.macrurusMerriam,1898—fromCBritishColumbiaStoEWashington,USA. M.l.sierraeKellogg,1922—fromtheOregonborderStoECCalifornia,USA. M. l. vellerosus J. A. Allen, 1899 — widely distributed from EC Alaska SE to SE British Columbia and SW Alberta, Canada. Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 342, DOI: 10.5281/zenodo.6707142